Estudio del proceso de rehidratación de las rocas metamórficas de la Formación Silgará a partir del análisis composicional de la Clorita, región suroccidental del Macizo de Santander (2002)
Chlorites in metamorphic rocks of the Silgará Formation that crop out in the southwestern region of the Santander Massif (Chicamocha Canyon) registre formation temperatures between 180 and 355°C. The maximun temperatures of formation of this hydrated mineral phase (up to 355°C) correspond to the highergrade metamorphic zone (staurolite-distene), while in the biotite and garnet (upper part) zones, these temperatures vary in average between 180 and 270°C. These values of temperature suggest a rehydration of the greater depth rocks rather than those from higher structural levels of the metamorphic pile. This process appears to be explained in an extensive deformation context, which has generated a major amount of anysotropy planes in depth, by which hydrothermal fluids circulated. Besides, the generation of these channels should be related to the incompetent behavior of these lithologies in a great part of the exhumation history of the this Formation.